Multiflow Model for Routing and Policing Traffic in Infocommunication Network - Mohammed Khodayer Hassan (International Journal of Engineering Inventions, 2014)
Thus the article offers the model represented by algebraic equations and inequalities for routing and policing traffic in infocommunication network. The novelty of the model is as follows: multiflow nature of modern ICN is taken into account (1), i.е. a set of flows circling between different pairs of network routers are considered simultaneously; coherent formalization of processes of traffic routing and policing within the model that has lower dimensionality in comparison to known earlier is provided; the choice of optimality criterion, use of which allows to implement multipath routing with consequent inclusion of paths as well as to organize limitation of flow intensity on all the used routs simultaneously depending on their characteristics and flow priority. According to the results of the analysis conducted we offer recommendations for choosing relation in numerical values of routing metrics and service denial regarding the provision of the given values for the main QoS characteristics, e.g. average packet delay. The model can be used as a basis for perspective protocol decisions aimed at coherence of solutions for the tasks of traffic routing and policing. Further development of the given model is possible under full account of stochastic characteristics of packet flows circling in the network.Thus the article offers the model represented by algebraic equations and inequalities for routing and policing traffic in infocommunication network. The novelty of the model is as follows: multiflow nature of modern ICN is taken into account (1), i.е. a set of flows circling between different pairs of network routers are considered simultaneously; coherent formalization of processes of traffic routing and policing within the model that has lower dimensionality in comparison to known earlier is provided; the choice of optimality criterion, use of which allows to implement multipath routing with consequent inclusion of paths as well as to organize limitation of flow intensity on all the used routs simultaneously depending on their characteristics and flow priority. According to the results of the analysis conducted we offer recommendations for choosing relation in numerical values of routing metrics and service denial regarding the provision of the given values for the main QoS characteristics, e.g. average packet delay. The model can be used as a basis for perspective protocol decisions aimed at coherence of solutions for the tasks of traffic routing and policing. Further development of the given model is possible under full account of stochastic characteristics of packet flows circling in the network.
Keywords: Routing; Traffic; Flow; Priority; Quality of Service; Network